Catalyst, process for its preparation and use, and process for the preparation of methyl methacrylate

CN119972067BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311509042.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2026-10-30
Estimated Expiration
2043-11-13

AI Technical Summary

Technical Problem

[0004]本发明的目的是为了克服现有催化剂在甲基丙烯醛选择性氧化制取甲基丙烯酸甲酯反应中,存在MMA选择性低的问题,提供一种催化剂及其制备方法和应用、以及制备甲基丙烯酸甲酯的方法

Benefits of technology

[0014]通过上述技术方案,采用本发明Au基复合催化剂,通过调整催化剂活性组分与助活性组分之间的配比,以及催化剂活性组分与载体之间的配比,提高催化剂在甲基丙烯醛选择性氧化制得甲基丙烯酸甲酯反应中的活性,原料的转化率以及甲基丙烯酸甲酯的选择性。对本发明Au基复合催化剂进行性能评价(评价结果见表1),与对比例相比较,实施例制得的Au基复合催化剂具有较高的甲基丙烯酸甲酯的选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119972067B_ABST
    Figure CN119972067B_ABST
Patent Text Reader

Abstract

The present application relates to the field of methyl methacrylate preparation, in particular to a catalyst and its preparation method and application, and a method for preparing methyl methacrylate. The chemical general formula of the catalyst is Au-Y a / Si b Nd c D d O e , wherein D is at least one selected from Be, Mg, Ca, Sr, Ba, Al, Ga, In, Tl; a is the molar ratio of Y to Au, a = 0.1-1; b is the molar ratio of Si to Au, b = 10-200; c is the molar ratio of Nd to Au, c = 0.1-1; d is the molar ratio of D to Au, d = 1-50; e is the molar number of oxygen atoms required to satisfy the valence of each element in the active component. The catalyst is applied to the preparation of methyl methacrylate, and has high raw material conversion rate and selectivity of methyl methacrylate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of methyl methacrylate preparation, specifically to a catalyst, its preparation method and application, and a method for preparing methyl methacrylate. Background Technology

[0002] Methyl methacrylate (MMA), also known as methyl isobutylene acrylate, is an important organic chemical raw material. It is mainly used in the production of polymethyl methacrylate (PMMA, acrylic glass), the polyvinyl chloride (PVC) additive ACR, and as a second monomer in the production of acrylic fibers. It is also used in the manufacture of other resins, plastics, coatings, adhesives, lubricants, wood and cork impregnating agents, and paper varnishes. With the diversification and development of downstream MMA products, global demand and production capacity for MMA are continuously increasing.

[0003] Currently, global MMA production technology has evolved from the initial acetone cyanohydrin method to a more diversified approach in terms of raw materials and processes. The main production processes are the ACH, C4, and Alpha processes. ACH process facilities account for 59% of the world's total capacity, C4 for 31%, and Alpha for 9%. Different process routes offer varying levels of techno-economic viability. Among industrialized MMA production processes, the traditional ACH process is characterized by its simplicity and high maturity. However, the raw material used, hydrogen cyanide, is highly toxic, and both hydrogen cyanide and sulfuric acid are highly corrosive, requiring sophisticated reaction equipment and generating large amounts of waste acid, potentially causing significant environmental damage. Alpha technology is currently in its early stages of industrialization, and its technological maturity and overall economic viability require further evaluation. The C4 route directly uses air or oxygen as an oxidant to oxidize methacrolein and methanol into the target product MMA in one step. It is undoubtedly a simple, green, and economically competitive process route that will greatly save production costs. At the same time, the byproduct of this process is water, which is environmentally friendly. However, the difficulty of this process lies in the preparation of high-performance catalysts, especially catalysts with high activity, high methacrolein conversion rate, and high MMA selectivity, which has become a research hotspot for catalysts in this reaction. Summary of the Invention

[0004] The purpose of this invention is to overcome the problem of low MMA selectivity in the selective oxidation of methacrolein to methyl methacrylate using existing catalysts, and to provide a catalyst, its preparation method and application, as well as a method for preparing methyl methacrylate.

[0005] To achieve the above objectives, a first aspect of the present invention provides a catalyst, the catalyst having the general chemical formula Au-Y. a / Si b Nd c D d O eWherein, D is selected from at least one of Be, Mg, Ca, Sr, Ba, Al, Ga, In, and Tl; a is the molar ratio of Y to Au, a = 0.1-1; b is the molar ratio of Si to Au, b = 10-200; c is the molar ratio of Nd to Au, c = 0.1-1; d is the molar ratio of D to Au, d = 1-50; and e is the number of moles of oxygen atoms required to satisfy the oxidation states of each element in the active component.

[0006] A second aspect of the present invention provides a method for preparing the catalyst described in the first aspect, the method comprising the following steps:

[0007] (1) The solution containing Si, Nd and D elements is dried and first calcined to obtain the support;

[0008] (2) The support obtained in step (1) is mixed with a solution containing Au and Y elements, and then dried and calcined to obtain the catalyst.

[0009] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the method described in the second aspect in the selective oxidation of methacrolein to produce methyl methacrylate.

[0010] A fourth aspect of the present invention provides a method for preparing methyl methacrylate, the method comprising:

[0011] (1) The catalyst is activated to obtain the activated catalyst;

[0012] (2) In the presence of the activated catalyst obtained in step (1), methacrolein is reacted with methanol;

[0013] The catalyst is either the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect.

[0014] By employing the Au-based composite catalyst of this invention and adjusting the ratio between the active and co-active components, as well as the ratio between the active component and the support, the activity, conversion rate, and selectivity of the catalyst in the selective oxidation of methacrolein to methyl methacrylate are improved. The performance of the Au-based composite catalyst of this invention was evaluated (evaluation results are shown in Table 1). Compared with the comparative example, the Au-based composite catalyst prepared in the examples exhibits higher selectivity for methyl methacrylate. Attached Figure Description

[0015] Figure 1 The catalyst Au-Y prepared in Example 1 0.5 / Si 100 Nd 0.5 Al20 O e TEM image;

[0016] Figure 2 The catalyst Au-Y prepared in Example 6 0.5 / Si 100 Nd 0.5 Al2O e TEM image. Detailed Implementation

[0017] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0018] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0019] The first aspect of this invention provides a catalyst, the catalyst having the general chemical formula Au-Y. a / Si b Nd c D d O e Wherein, D is selected from at least one of Be, Mg, Ca, Sr, Ba, Al, Ga, In, and Tl; a is the molar ratio of Y to Au, a = 0.1-1; b is the molar ratio of Si to Au, b = 10-200; c is the molar ratio of Nd to Au, c = 0.1-1; d is the molar ratio of D to Au, d = 1-50; and e is the number of moles of oxygen atoms required to satisfy the oxidation states of each element in the active component.

[0020] According to the present invention, the catalyst of the present invention has the general chemical formula Au-Y a / Si b Nd c D d O e In the preferred embodiment, a = 0.2-0.5.

[0021] According to the present invention, the catalyst of the present invention has the general chemical formula Au-Y a / Si b Nd c D d O e In the preferred embodiment, b = 50-100.

[0022] According to the present invention, the catalyst of the present invention has the general chemical formula Au-Y a / Si b Nd c D d O e In the preferred embodiment, c = 0.2-0.5.

[0023] According to the present invention, the catalyst of the present invention has the general chemical formula Au-Y a / Si b Nd c D d O e In the preferred embodiment, d = 10-30.

[0024] Using the catalyst composition described in the preferred embodiment above, a higher feed conversion rate and MMA selectivity are achieved when catalytically oxidizing methacrolein to prepare methyl methyl propionate (MMA).

[0025] According to the present invention, in order to achieve a high yield of methyl methacrylate (MMA) when the catalyst is applied to the selective oxidation of methacrolein, the ratio of d to a is (10-100):1; preferably, the ratio of d to a is (20-80):1; more preferably, the ratio of d to a is (20-60):1; and even more preferably, the ratio of d to a is (30-50):1.

[0026] According to the present invention, preferably, the active components of the catalyst are Au and Y, and the catalyst support contains Si, Nd and D.

[0027] Preferably, the average particle size of the catalyst active component is 4.5-4.7 nm.

[0028] In this invention, the particle size of the catalyst active component refers to the maximum straight-line distance between any two different points on the particle. For example, when the particle is spherical, the particle size refers to its diameter.

[0029] The particle size of the active component of the catalyst in this invention was obtained by transmission electron microscopy (TEM). The average particle size was obtained by averaging the particle sizes of 200 particles.

[0030] Preferably, D is selected from at least one of Mg, Ca, Sr, Ba, and Al, and more preferably Mg or Al.

[0031] Preferably, the mass ratio of the active component of the catalyst to the catalyst support is 0.51-3.96: 99.49-96.04.

[0032] According to the present invention, in order to increase the contact area between the active component particles of the catalyst and the reactants in the reaction and improve the catalytic performance of the catalyst, preferably, based on the total number of active component particles of the catalyst, the proportion of active component particles with a particle size of 4-5 nm is 90-95%; more preferably, the proportion r1 of active component particles with a particle size of 4-4.5 nm is 40-45%, and the proportion r2 of active component particles with a particle size of 4.5-5 nm is 45-50%.

[0033] In this invention, a particle size of 4.5 nm is included in the range of 4-4.5 nm, but is no longer included in the range of 4.5-5 nm.

[0034] Preferably, the ratio of r2 to r1 is (1-1.1):1.

[0035] The particle size of the active component of the catalyst in this invention was obtained by testing 200 particles using transmission electron microscopy (TEM).

[0036] In this invention, the composition of the catalyst is obtained by inductively coupled plasma spectroscopy (ICP) testing or by calculating the amount of feed during the preparation process.

[0037] A second aspect of the present invention provides a method for preparing the catalyst described in the first aspect, the method comprising the following steps:

[0038] (1) The solution containing Si, Nd and D elements is dried and first calcined to obtain the support;

[0039] (2) The support obtained in step (1) is mixed with a solution containing Au and Y elements, and then dried and calcined to obtain the catalyst.

[0040] According to the preparation method of the present invention, by adjusting the ratio between the catalyst active component precursor and the co-active component precursor, and the ratio between the catalyst active component precursor and the support precursor, the obtained catalyst has higher catalytic activity and selectivity for methyl methacrylate in the selective oxidation of methacrolein to methyl methacrylate.

[0041] According to the preparation method of the present invention, in order to form a carrier with a specific structure and uniform element distribution, preferably, the solution containing Si, Nd and D elements is obtained by mixing a solution containing Si and Nd elements with a solution containing D elements.

[0042] Preferably, the solution containing Si and Nd elements is aged before mixing.

[0043] Preferably, the aging conditions include stirring at a temperature of 80-150°C for 6-30 hours. The present invention does not impose a particular limitation on the stirring speed, which can be selected by those skilled in the art using conventional methods.

[0044] According to the preparation method of the present invention, there is no particular limitation on the source of each element in the solution containing Si, Nd and D and the solution containing Au and Y, and they can each come from a compound containing that element.

[0045] Preferably, the Si element is derived from at least one of silica sol, colloidal silica, ethyl silicate, and silica powder.

[0046] In this invention, the Nd element can be derived from a soluble salt containing Nd.

[0047] Preferably, the Nd element is derived from at least one of neodymium nitrate, neodymium oxide, neodymium phosphate, and neodymium thorium.

[0048] In this invention, the element D can be derived from a soluble salt containing the element D, wherein the soluble salt containing the element D is at least one of Be salt, Mg salt, Ca salt, Sr salt, Ba salt, Al salt, Ga salt, In salt, and Tl salt.

[0049] Preferably, the D element is derived from at least one of aluminum nitrate, aluminum phosphate, boehmite, aluminum isopropoxide, and magnesium nitrate.

[0050] According to the preparation method of the present invention, in order to make the elements and active loading sites on the carrier surface more uniform, preferably, in step (1), the drying is spray drying, and more preferably, the spray drying temperature is 100-180℃ and the time is 1-12h.

[0051] According to the preparation method of the present invention, preferably, in step (1), the temperature of the first calcination is 500-700℃ and the time is 6-48h.

[0052] More preferably, the first calcination temperature is 550-650℃ and the time is 6-24h.

[0053] Preferably, the first calcination is carried out in an oxygen-free atmosphere; more preferably, an inert atmosphere, such as at least one of nitrogen, argon, neon and helium.

[0054] According to the preparation method of the present invention, there are no particular limitations on the preparation method of the solution containing Au and Y elements. In order to make the active sites more uniform, preferably, in step (2), the solution containing Au and Y elements is obtained by mixing the solution containing Y elements with the solution containing Au elements. The present invention has a wide range of selection for the addition rate of the solution containing Y elements, and those skilled in the art can make an adaptive selection according to actual production. More preferably, the addition rate of the solution containing Y elements is 1-20 mL / min.

[0055] Preferably, the mixing temperature of the solution containing Y and the solution containing Au is not higher than 50°C, and more preferably 30-50°C.

[0056] According to the preparation method of the present invention, preferably, in step (2), the Au element is derived from at least one of chloroauric acid, gold trichloride hydrate, and potassium tetrachloroaurate hydrate.

[0057] According to the preparation method of the present invention, preferably, the Y element is derived from at least one of yttrium nitrate, yttrium acetate, and yttrium phosphate.

[0058] According to the preparation method of the present invention, preferably, in step (2), the temperature for mixing the carrier obtained in step (1) with the solution containing Au and Y elements is 30-80°C and the time is 0.5-5h.

[0059] Preferably, in step (2), the second roasting temperature is 300-500℃ and the time is 6-48h.

[0060] More preferably, the second calcination temperature is 350-450℃ and the time is 8-15h.

[0061] Preferably, the second calcination is carried out in an oxygen-free atmosphere; more preferably, an inert atmosphere, such as at least one of nitrogen, argon, neon and helium.

[0062] In the preparation method provided by the present invention, those skilled in the art can adaptively select the amount of each substance to be added based on the amount of each component in the target catalyst.

[0063] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the method described in the second aspect in the selective oxidation of methacrolein to produce methyl methacrylate.

[0064] A fourth aspect of the present invention provides a method for preparing methyl methacrylate, the method comprising:

[0065] (1) The catalyst is activated to obtain the activated catalyst;

[0066] (2) In the presence of the activated catalyst obtained in step (1), methacrolein is reacted with methanol;

[0067] The catalyst is either the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect.

[0068] According to the present invention, in order to improve the catalytic activity of the catalyst and increase the yield of methyl methacrylate, when preparing methyl methacrylate using the catalyst provided in the first aspect of the present invention, the catalyst is activated. Preferably, the activation conditions include: being carried out under an inert atmosphere, with an activation temperature of 50-100°C and an activation time of 6-48 h. More preferably, the inert atmosphere is at least one of nitrogen, argon, neon, and helium.

[0069] According to the present invention, in order to promote the mutual reaction between methacrolein and methanol and improve the conversion rate of methacrolein and the yield of methyl methacrylate, preferably, in step (2), the reaction conditions include: a molar ratio of methacrolein to methanol of 20-40:1-2, a temperature of 50-100℃, a pressure of 1-10MPa, and a time of 1-10h.

[0070] The present invention will be described in detail below through embodiments.

[0071] Example 1

[0072] (1) A silica sol containing 10 mol Si (molecular formula: SiO2) and a neodymium nitrate solution containing 0.05 mol Nd (molecular formula: Nd(NO3)3) were mixed and aged at 100°C for 10 h. Then, an aluminum nitrate solution containing 2 mol Al (molecular formula: Al(NO3)3) was added and stirred at 80°C for 3 h. After stirring evenly, the mixture was spray-dried at 150°C and then calcined at 600°C for 12 h under a nitrogen atmosphere to obtain the support.

[0073] (2) Dissolve 0.1 mol of chloroauric acid (molecular formula: HAuCl4) and 0.05 mol of yttrium nitrate (molecular formula: Y(NO3)3) in deionized water at 40℃. Under stirring, slowly add the yttrium nitrate solution to the chloroauric acid solution at a rate of 10 mL / min, and then continue stirring for 3 h. After mixing evenly, obtain mixture I. Add mixture I and the support prepared in step (1) to a flask, mix evenly, stir for 2 h under oil bath conditions at 80℃, and wash the mixture after cooling to obtain the catalyst precursor. Dry the catalyst precursor in a vacuum oven at 100℃ for 3 h, and then calcine it in a muffle furnace at 400℃ for 12 h under nitrogen atmosphere to obtain the catalyst with the following composition: Au-Y 0.5 / Si100 Nd 0.5 Al 20 O e .

[0074] Figure 1 The TEM image of the catalyst prepared in Example 1 is shown below. Figure 1 It can be seen that the catalyst Au-Y 0.5 / Si 100 Nd 0.5 Al 20 O e The supported active components have small particle sizes, with an average particle size of 4.6 nm; the active component particles are well dispersed on the surface of the catalyst support.

[0075] Example 2

[0076] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.5 / Si 100 Nd 0.5 Al5O e .

[0077] Example 3

[0078] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.5 / Si 100 Nd 0.5 Al 50 O e .

[0079] Example 4

[0080] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.5 / Si 100 Nd 0.5 Al 15 O e .

[0081] Example 5

[0082] Following the method in Example 1, 2 mol of aluminum nitrate was replaced with 2 mol of magnesium nitrate to prepare a catalyst with the following composition: Au-Y 0.5 / Si 100 Nd 0.5 Mg 20 O e .

[0083] Example 6

[0084] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y0.5 / Si 100 Nd 0.5 Al2O e .

[0085] Figure 2 The TEM image of the catalyst prepared in Example 6 is shown below. Figure 2 It can be seen that the catalyst Au-Y 0.5 / Si 100 Nd 0.5 Al2O e The particle size of the supported active component is not uniform, and the particle size is larger, with an average particle size of 4.9 nm; the dispersibility of the active component particles on the surface of the catalyst support is poor.

[0086] Example 7

[0087] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.2 / Si 100 Nd 0.5 Al8O e .

[0088] Example 8

[0089] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.5 / Si 50 Nd 0.5 Al 20 O e .

[0090] Example 9

[0091] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.5 / Si 100 Nd 0.2 Al 20 O e .

[0092] Comparative Example 1

[0093] Following the method of Example 1, 0.1 mol of chloroauric acid and 0.05 mol of yttrium nitrate were replaced with 0.15 mol of chloroauric acid to prepare a catalyst with the following composition: Au 1.5 / Si 100 Nd 0.5 Al 20 O e .

[0094] Comparative Example 2

[0095] Following the method of Example 1, by changing the feed ratio, a catalyst with the following composition was prepared: Au-Y 0.5 / Si 100 Nd 0.5 Al 75 O e。

[0096] Test case

[0097] The catalysts prepared in the examples and comparative examples were subjected to TEM testing to obtain the size of the active component particles of the catalysts. The test results are shown in Table 1.

[0098] The catalysts prepared in the examples and comparative examples were placed in a nitrogen atmosphere and activated at 80°C for 12 hours. The catalysts were evaluated, and the results are shown in Table 1. The catalyst evaluation method is as follows:

[0099] Reactor: Stirred tank reactor, volume 250ml;

[0100] Catalyst loading: 2g;

[0101] Reaction temperature: 80℃;

[0102] Reaction pressure: 3 MPa;

[0103] Reaction time: 3 hours;

[0104] Raw material molar ratio: methanol / methacrylaldehyde = 25;

[0105] Feed amounts: 1.69 mol methanol, 0.067 mol methacrolein.

[0106] Table 1

[0107]

[0108]

[0109] As can be seen from Table 1, when the catalysts prepared in Examples 1-9 and Comparative Examples 1-2 are applied to the selective catalytic oxidation of methacrolein, under the same conditions, compared with the catalyst whose active component is only Au, the catalyst whose active component contains Au and Y has a smaller average particle size of the active component and better dispersibility on the support, which can significantly improve the conversion rate of the catalyst and the selectivity of methyl methacrylate (MMA).

[0110] Comparing the catalyst prepared in Example 1 with the catalysts prepared in Examples 2-4 and 6, it can be seen that the ratio of d to a in the catalyst affects the average particle size of the prepared catalyst. Under the same conditions, when the ratio of d to a in the catalyst is 40:1, the particle size of the catalyst is the most concentrated and the yield of MMA is also the highest.

[0111] Comparing Example 1 and Example 5, when D in the catalyst is Al, the catalyst has a higher feed conversion rate and MMA selectivity.

[0112] As can also be seen from Table 1, activating the catalyst prepared in Example 1 before its application in the preparation of methyl methacrylate can significantly improve the catalytic activity of the catalyst and the yield of methyl methacrylate.

[0113] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A catalyst, characterized in that, The general chemical formula of the catalyst is Au-Y. a / Si b Nd c D d O e The catalyst's active components are Au and Y, and the catalyst support contains Si, Nd, and D; D is selected from at least one of Be, Mg, Ca, Sr, Ba, Al, Ga, In, and Tl; a is the molar ratio of Y to Au, a = 0.1-1; b is the molar ratio of Si to Au, b = 10-200; c is the molar ratio of Nd to Au, c = 0.1-1; d is the molar ratio of D to Au, d = 1-50; e is the number of moles of oxygen atoms required to satisfy the valence of each element in the active components; the ratio of d to a is (10-100):

1. The average particle size of the active component of the catalyst is 4.5-4.7 nm.

2. The catalyst according to claim 1, wherein, a=0.2-0.5; b=50-100; c=0.2-0.5; d=10-30.

3. The catalyst according to claim 1, wherein, The ratio of d to a is (20-80):

1.

4. The catalyst according to claim 3, wherein, The ratio of d to a is (20-60):

1.

5. The catalyst according to claim 4, wherein, The ratio of d to a is (30-50):

1.

6. The catalyst according to any one of claims 1-5, wherein, D is selected from at least one of Mg, Ca, Sr, Ba, and Al.

7. The catalyst according to claim 1, wherein, The mass ratio of the active component to the catalyst support in the catalyst is 0.51-3.96: 99.49-96.

04.

8. The catalyst according to claim 1, wherein, Based on the total number of active components of the catalyst, the proportion of active component particles r1 of the catalyst with a particle size of 4-4.5 nm is 40-45%, the proportion of active component particles r2 of the catalyst with a particle size of 4.5-5 nm is 45-50%, and the proportion of active component particles of the catalyst with a particle size of 4-5 nm is 90-95%.

9. The catalyst according to claim 8, wherein, The ratio of r2 to r1 is (1-1.1):

1.

10. A method for preparing the catalyst according to any one of claims 1-9, the method comprising the following steps: (1) The solution containing Si, Nd and D elements is dried and first calcined to obtain the support; (2) The support obtained in step (1) is mixed with a solution containing Au and Y elements, and then dried and calcined to obtain the catalyst.

11. The method according to claim 10, wherein, The solution containing Si, Nd, and D elements is obtained by mixing a solution containing Si and Nd elements with a solution containing D element.

12. The method according to claim 11, wherein, Before mixing, the solution containing Si and Nd elements is aged.

13. The method according to claim 12, wherein, The aging conditions include stirring at a temperature of 80-150℃ for 6-30 hours.

14. The method according to any one of claims 10-13, wherein, The Si element is derived from at least one of silica sol, ethyl silicate, and silicon dioxide; And / or, the Nd element is derived from at least one of neodymium nitrate, neodymium oxide, neodymium phosphate, and neodymium thorium nitrate; And / or, the element D is derived from at least one of aluminum nitrate, aluminum phosphate, boehmite, and aluminum isopropoxide.

15. The method according to any one of claims 10-13, wherein, In step (1), the drying is spray drying.

16. The method according to claim 15, wherein, The spray drying temperature is 100-180℃, and the time is 1-12h.

17. The method according to any one of claims 10-13, wherein, In step (1), the temperature of the first roasting is 500-700℃ and the time is 6-48 h.

18. The method according to claim 17, wherein, The first calcination was carried out in an oxygen-free atmosphere.

19. The method according to any one of claims 10-13, wherein, In step (2), the solution containing Au and Y elements is obtained by mixing a solution containing Y elements with a solution containing Au elements.

20. The method according to claim 19, wherein, The solution containing Y element is added at a rate of 1-20 mL / min.

21. The method according to claim 20, wherein, The mixing temperature of the solution containing Y and the solution containing Au shall not exceed 50°C.

22. The method according to claim 21, wherein, The mixing temperature of the solution containing Y and the solution containing Au is 30-50℃.

23. The method according to any one of claims 10-13, wherein, In step (2), the Au element is derived from at least one of chloroauric acid, gold trichloride hydrate, and potassium tetrachloroaurate hydrate; And / or, the Y element is derived from at least one of yttrium nitrate, yttrium acetate, and yttrium phosphate.

24. The method according to any one of claims 10-13, wherein, The carrier obtained in step (1) is mixed with a solution containing Au and Y elements at a temperature of 30-80℃ for 0.5-5h. And / or, in step (2), the second calcination temperature is 300-500℃ and the time is 6-48h; The second calcination is carried out in an oxygen-free atmosphere.

25. The use of a catalyst according to any one of claims 1-9 or a catalyst prepared by any one of claims 10-24 in the selective oxidation of methacrolein to methyl methacrylate.

26. A method for preparing methyl methacrylate, characterized in that, The method includes: (1) The catalyst is activated to obtain the activated catalyst; (2) In the presence of the activated catalyst obtained in step (1), methacrolein is reacted with methanol; The catalyst is the catalyst according to any one of claims 1-9 or the catalyst prepared by the preparation method according to any one of claims 10-24.

27. The method according to claim 26, wherein, In step (1), the activation conditions include: being carried out under an inert atmosphere, with an activation temperature of 50-100℃ and an activation time of 6-48h; And / or, in step (2), the reaction conditions include: a molar ratio of methacrolein to methanol of 20-40:1-2, a temperature of 50-100℃, a pressure of 1-10MPa, and a time of 1-10h.

Citation Information

Patent Citations

  • Catalyst to produce methyl methacrylate efficiently at low cost and preparation method of catalyst

    CN109395732A